Cues for seizure timing. Issue Volume 62:Issue S1(2021)Supplement (1st August 2020) - Rao, Vikram R.; G. Leguia, Marc; Tcheng, Thomas K.; Baud, Maxime O.
Abstract: The cyclical organization of seizures in epilepsy has been described since antiquity. However, historical explanations for seizure cycles—based on celestial, hormonal, and environmental factors—have only recently become testable with the advent of chronic electroencephalography (cEEG) and modern statistical techniques. Here, factors purported over millennia to influence seizure timing are viewed through a contemporary lens. We discuss the emerging concept that seizures are organized over multiple timescales, each involving differential influences of external and endogenous rhythm generators. Leveraging large cEEG datasets and circular statistics appropriate for cyclical phenomena, we present new evidence for circadian (day‐night), multidien (multi‐day), and circannual (about‐yearly) variation in seizure activity. Modulation of seizure timing by multiscale temporal variables has implications for diagnosis and therapy in clinical epilepsy. Uncovering the mechanistic basis for seizure cycles, particularly the factors that govern multidien periodicity, will be a major focus of future work.